Learning From Indigenous Perspectives: Wellbeing in the Early Years (LEARNing Landscapes, 2024)
This three-year qualitative research study examined the knowledge and experiences of 20 early years educators while introducing Indigenous perspectives and pedagogies on Land-Based Learning in 10 urban childcare centers. Educators were introduced to Indigenous perspectives and pedagogies through workshops with Indigenous speakers and Indigenous-authored picture books. These perspectives included the importance of supporting children to develop responsive and caring relationships to the Land for their own wellbeing and for the wellbeing of all their fellow creatures. Supported by their educators, the children increased their sense of belonging in the world, expressed gratitude for their fellow creatures, and recognized and enacted their responsibility to care for nature.
Keywords: Wellbeing; Land-Based Learning; Indigenous Perspectives; Early Childhood; Early Childhood Educator; Preschool; Childcare; Outdoor Pedagogy; Nature-Based Pedagogy; Environmental Inquiry